Analyzing the Impact of Corporate Governance Practices and Disclosures on the Financial Performance of the Textile Industry in India - Soni, Anurag (2009)
Corporations in modern day practice have been regulated by both the regulator and shareholders on how well the company is governed. Fall of companies like WorldCom, Enron and Satyam have raised the issue of corporate governance practiced followed by corporations the world over. In the Indian context with the rise in corporate scandals, SEBI has been regulating the operations of corporations and have introduced Clause 49 Listing Agreement and every Indian public listed company needs to comply with the same. On the other hand there are certain voluntary disclosures which the corporations can make on their own will to gain shareholder confidence and trust. This thesis would present a study on the impact of corporate governance practices and disclosures on the financial value of the textile industry in India. The paper would study the corporate governance factors like board size, independent directors and number of disclosures which have an impact on the financial value of the measured which would be measured by Return on Assets, Return on Equity and Earnings per Share. The thesis would be studied over a period of four years from 2005-06 to 2008-09. The research has been based on secondary information from reliable sources which would provide accurate findings. Overall the research focuses on concluding whether corporate governance practices have a positive impact or a negative impact on the financial value of textile firms in India.